1987
DOI: 10.1366/0003702874449011
|View full text |Cite
|
Sign up to set email alerts
|

Background Correction in Multicomponent Spectroscopic Analysis Using Target Transformation Factor Analysis

Abstract: A principal components regression (PCR) is used to construct a calibration matrix for multicomponent spectroscopic analysis which corrects for background absorption due to variable concentrations of unknown species in a sample matrix. Mixed standards are used in the method, and spectra of the pure background components are not needed. The background correction capability of the method is demonstrated with the use of the UV spectra of aqueous standards prepared from cobalt (II) nitrate and nickel (II) nitrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…is the RMS spectral error for the reproduced data matrix. 8 In Table 1, if a one-factor model is used, the estimated spectral error is about 0-014 absorbance units, which is much greater than the measurement noise expected from the HP8452A diode array spectrometer used in this work. If a two-factor model is used, the estimated spectral error is about 040008 absorbance units, which corresponds nicely with the anticipated spectral error for the HP8452A.…”
Section: Theorymentioning
confidence: 75%
“…is the RMS spectral error for the reproduced data matrix. 8 In Table 1, if a one-factor model is used, the estimated spectral error is about 0-014 absorbance units, which is much greater than the measurement noise expected from the HP8452A diode array spectrometer used in this work. If a two-factor model is used, the estimated spectral error is about 040008 absorbance units, which corresponds nicely with the anticipated spectral error for the HP8452A.…”
Section: Theorymentioning
confidence: 75%
“…Background Calibration-Factor Analysis-Target Transformation. This method of factor analysis has been described by Gemperline and co-workers in a recent publication (13). These authors reported good results for the determination of component concentrations in the presence of a variable background contribution, provided that the background components were present in a calibration data set.…”
Section: Resultsmentioning
confidence: 99%
“…The probability level from the F-test was used to identify unacceptable test vectors. Fredericks el al.," Brown et al 43 and Gemperline et al 44 recognized that the residual sum of squares for response variables could be used to detect invalid samples in principal component regression. Haaland and Thomas also reported an F-test for PCR and PLS that can be used to detect invalid samples.…”
Section: Detection Of Invalid Samplesmentioning
confidence: 99%